2021
DOI: 10.1136/bjophthalmol-2020-318293
|View full text |Cite
|
Sign up to set email alerts
|

Low fraction of fetal haemoglobin is associated with retinopathy of prematurity in the very preterm infant

Abstract: BackgroundBlood loss and adult blood transfusions are common during the neonatal period in preterm infants. The objective of the study was to clarify if degree of loss of fetal haemoglobin (HbF) was associated with later retinopathy of prematurity (ROP).MethodsRetrospective observational cohort study. In total, 452 infants born <30 gestational weeks at a tertiary level neonatal intensive care unit in Sweden in 2009–2015 were included, 385 of whom had final ROP outcome. Mean fractions of HbF (%) during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The authors found that in comparison with neonates without ROP, the 104 neonates developing any stage of ROP had equivalent HbF at birth but lower HbF levels in the first postnatal week. The probability for developing any ROP was about 60% in neonates with a mean HbF value of 40% in the first week of life, compared with only a 10% probability in those with a mean HbF value of 90% ( 31 ). Considering that the GA of enrolled patients was 26.4 ± 1.7 weeks, these findings strongly suggest that low-HbF-related causal mechanisms of ROP operate at a PMA lower than 31 weeks, in contrast to what Lust et al suggested ( 27 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The authors found that in comparison with neonates without ROP, the 104 neonates developing any stage of ROP had equivalent HbF at birth but lower HbF levels in the first postnatal week. The probability for developing any ROP was about 60% in neonates with a mean HbF value of 40% in the first week of life, compared with only a 10% probability in those with a mean HbF value of 90% ( 31 ). Considering that the GA of enrolled patients was 26.4 ± 1.7 weeks, these findings strongly suggest that low-HbF-related causal mechanisms of ROP operate at a PMA lower than 31 weeks, in contrast to what Lust et al suggested ( 27 ).…”
Section: Discussionmentioning
confidence: 97%
“…The association between repeated transfusions and ROP is supported by robust scientific evidence ( 7 – 9 , 16 , 25 28 ). The risk for developing ROP seems to be higher if RBC transfusions are administered at an early period of life ( 27 , 29 31 ). In this regard, the findings emerging in the present study highlight two main points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Hellström et al (retrospectively study including 385 infants born at GA ≤ 30 weeks) found that neonates developing any stage of ROP had equivalent HbF at birth but lower HbF levels in the rst postnatal week. 24 The probability of ROP was about 60% in neonates with a mean HbF value of 40%, compared to only 10% probability in those with a mean HbF value of 90%. 24 RBC transfusions represent the mainstay for treating prematurity anemia and are unavoidable for most patients.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, using UCB for transfusions instead of blood from adult donors could be an alternative to reduce anemia and the risk for hyperoxemia and fluctuating oxygenation which are prominent risk factors for neonatal morbidities. In accordance, frequent diagnostic blood sampling in combination with blood transfusions in very preterm infants has been associated with an increased risk for neonatal morbidities such as bronchopulmonary dysplasia (BPD) and rethinopathy of prematurity (ROP) [21,22]. ROP is a leading cause of childhood blindness worldwide; 1.2 percent of premature infants (year 2010) developed ROP [23,24].…”
Section: Introductionmentioning
confidence: 99%